Performance research of the T′ algorithm over GF（2） - GUO Wen-ping 1; AN Jin-liang2 (Tongxin xuebao)
The XSL algorithm is a method for solving systems of multivariate polynomial equations based on the linearization method on GF（2）,and the T ’ method is the final stage of the XSL algorithm before linearization.Through analysis revealed that the T ’ algorithm can not achieve its desired end condition Free = T or Free=T-1.In orde to solve the problem,a real end condition and two variable selection principle was proposed for T′ algorithm.Based on probabilistic algorithms and variable values greater probability estimation method to improve performance of the original T ’algorithm.The results show that the improved T ’algorithm can simplify the equations.